2021
DOI: 10.1038/s41430-021-00904-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity on course and outcome of pregnancy from pre- to postnatal

Abstract: A healthy lifestyle that includes physical activity has numerous positive effects on the mother and child during and after pregnancy. In this context physical activity plays a central role due to its influence on body composition. While visceral fatty tissue has a pro-inflammatory effect via so-called adipokines, myokines seem to have a more anti-inflammatory effect and thus prevent numerous diseases such as gestational hypertension or gestational diabetes. However, many women show a decreased level of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 90 publications
1
31
1
11
Order By: Relevance
“…Due to the many benefits of regular activity during the perinatal period, pregnant women often modify their previous behavior and adapt to principles of a healthy lifestyle [ 41 ]. Nevertheless, pain, fear of harming the baby and of miscarriage or premature birth, in addition to fear of suffering an injury and lacking sufficient knowledge, are some of the most commonly reported reasons for not being active during pregnancy [ 42 , 43 ]. Changes in the level of physical activity may also be caused by the development of anxiety and depressive disorders [ 44 ], which may worsen as a result of the current pandemic state [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the many benefits of regular activity during the perinatal period, pregnant women often modify their previous behavior and adapt to principles of a healthy lifestyle [ 41 ]. Nevertheless, pain, fear of harming the baby and of miscarriage or premature birth, in addition to fear of suffering an injury and lacking sufficient knowledge, are some of the most commonly reported reasons for not being active during pregnancy [ 42 , 43 ]. Changes in the level of physical activity may also be caused by the development of anxiety and depressive disorders [ 44 ], which may worsen as a result of the current pandemic state [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nonpregnant nulliparous women had a significantly lower HBL and significantly lower perceived susceptibility, severity, benefits, and barriers scores than pregnant women, which aligns with our hypothesis. They had lower awareness of the hazards associated with inactivity, which may lead to prenatal physical inactivity, harming their health and that of their unborn children or causing illness when they become pregnant [ 6 ]. Janakiraman et al [ 28 ] discovered that women who were educated about the advantages and hazards of PA, the dangers of inactivity, and various exercise methods exhibited more favorable attitudes toward PPA.…”
Section: Discussionmentioning
confidence: 99%
“…The maternal advantages of exercise include increased fitness; avoidance of excessive pregnancy weight gain, weight retention, and possibly obesity, gestational diabetes, hypertension, and maternal depression [ 5 ]; and a decrease in cesarean-section rates [ 4 ]. Maternal exercise is also related to healthy birth weight and the prevention of chronic illness in children [ 6 ]. Recent studies have shown that maternal physical activity (PA) plays a positive role in the modulation of the progeny’s phenotype, giving the offspring improved health potential [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits associated with physical activity during pregnancy for both maternal and new-born health are supported by research [ 1 , 2 , 3 , 4 ]. For example, regular physical activity during pregnancy has been linked to reduced risk of weight gain [ 5 ], hypertension [ 6 ], diabetes [ 5 , 6 ], back pain [ 7 ], mood disorders [ 8 , 9 ], large for gestational age [ 3 ], premature birth [ 3 ], and caesarean sections [ 2 ].…”
Section: Introductionmentioning
confidence: 99%